Effect mechanism of Er content variations on the mechanical and corrosion properties of T6 state Al–Mg–Si-xEr sheets - Cao, Puli (2024)
This work investigates the influence of erbium (Er) content on the microstructure, mechanical properties, and corrosion behavior of T6 state AA6061 sheets. The findings reveal that nanoscale Al(Fe, Mn)Si particles are the main factors hindering dislocation motion and grain boundaries (GBs) migration. The addition of an appropriate amount of Er (0.6 wt%) effectively inhibits the precipitation of nanoscale Al(Fe, Mn)Si particles, promoting dislocation motion and grain boundary migration, thus significantly enhancing the alloy's plasticity. Furthermore, the sufficient migration of GBs leads to an increase in grain size, significantly reducing the quantity of GBs. This reduces the path for the propagation of corrosion cracks, resulting in improved corrosion resistance. Simultaneously, the addition of an appropriate amount of Er refines the coarse iron-rich phases into short rod-shaped Er-containing iron-rich phases with lower height and potential. This enables the alloy to obtain a more uniform oxide film and significantly reduces the tendency for microgalvanic corrosion, which is conducive to slowing down the initiation of corrosion. However, excessive Er addition (0.8–1.4 wt%) lead to the extensive precipitation of Er-containing iron-rich phases and nanoscale Al(Fe, Mn)Si particles, along with a continuous increase in the number of GBs, adversely affecting the plasticity and corrosion resistance of the alloy. This work offers a new strategy for obtaining 6XXX series alloys with excellent plasticity and corrosion resistance.